OPTIMIZATION OF MATHEMATICAL FUNCTION WITH SIMULATED ANNEALING METHOD USING COMMON LISP PROGRAMMING LANGUAGE - FITRA PERDANA (NIM : 10211108), PRABA
Optimization is something very useful for the process of planning in radiotherapy,which is to calculate and to achieve the best safe treatment for patient. In this research, an optimization program for mathematical function will be made using Common Lisp programming language and the program will be tested to see its feasibility for further development. Optimization technique used for this program is simulated annealing. The research was done by studying a certain optimization program using simulated annealing from reference which was made using MATLAB programming language. The program then translated into Common Lisp programming language and then tested into four testing method. From the tests, it was resulted that the slower the temperature variable rate as the program working, the better result in accuracy and precision will be obtained, then simulated annealing method was independent of the initial guess, mu inverse sampling algorithm was suitable to how simulated annealing works, and then finally the Common Lisp-made program performed better than MATLAB-made program. These results showed compatibility to the references.